1971
DOI: 10.1104/pp.48.5.575
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration, Water Fluxes, and Permeability of Tobacco Leaf Tissue

Abstract: Removal of the lower epidermis from a tobacco leaf allows a faster and wider range of water fluxes, without damaging the mesophyll. It also permits a more direct examination of the photosynthetic potential of the tissue at various levels of hydration.The rehydration rate of leaf discs is essentially linear. It decreases with leaf age and is correlated with the rate of dehydration, but it is independent of the tissue's water potential, as estimated by the isopiestic method. The hydraulic permeability coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Phospholipids play an important role in membrane permeability, mitochondrial electron transport (Green and Tzagoloff 1966) and Hill reaction (Hirayama and Nushida 1978) and subsequently any reduction in phospholipids will affect a variety of organelle functions. The phospholipid loss is also known to occur under several adverse climatic conditions such as dehydration (Graziane and Livne 1971), chilling (Lurie et al 1994), freezing (Lea and Hawke 1952), drought (Navari-Izzo et al 1993) and senescence (Brown et al 1994). This decrease in phospholipid may be due either to reduction in the power of hydrophobic proteins to bind phospholipids (Heber and Sanatarius 1964) or to lipid peroxidation on enhanced lecithinase (Harrison and Trevelyan 1963).…”
Section: Resultsmentioning
confidence: 99%
“…Phospholipids play an important role in membrane permeability, mitochondrial electron transport (Green and Tzagoloff 1966) and Hill reaction (Hirayama and Nushida 1978) and subsequently any reduction in phospholipids will affect a variety of organelle functions. The phospholipid loss is also known to occur under several adverse climatic conditions such as dehydration (Graziane and Livne 1971), chilling (Lurie et al 1994), freezing (Lea and Hawke 1952), drought (Navari-Izzo et al 1993) and senescence (Brown et al 1994). This decrease in phospholipid may be due either to reduction in the power of hydrophobic proteins to bind phospholipids (Heber and Sanatarius 1964) or to lipid peroxidation on enhanced lecithinase (Harrison and Trevelyan 1963).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that in silver maple seeds and areca palm embryos, which are desiccation-sensitive tissues at maturity, a similar increase in leakage and decrease in viability occurred below a critical moisture content; 40%Yo in silver maple seeds and 55% in areca palm embryos. Studies on foliar tissue also provide evidence that solute leakage from dehydrated tissue serves as a measure of dehydration-induced stress damage to membranes (5,11). Our results are complementary to these findings and consistent with the concept that membranes of desiccation-sensitive seeds are damaged by dehydration below a critical moisture content and do not become effective barriers to solute leakage during imbibition.…”
Section: Methodsmentioning
confidence: 99%
“…However, several factors influence stomatal function, and therefore, the degree to which ABA influences these processes is uncertain. Closure of stomata can occur within 10 min in excised leaf tissue (5 (14) associated low relative humidities with increases in ABA, but they attributed this influence to changes in leaf water status. Wright (22) concluded that high light intensities probably influenced ABA by inducing wilt.…”
Section: Methodsmentioning
confidence: 99%